PPP1R2 COORDINATES KINASE AND PHOSPHATASE ACTIVITY TO REGULATE THE CENTROSOME AND MIDBODY - Bresch, Alan-Michael (East Carolina University, 2021)
Centrosomes are the primary microtubule organizing centers of the cell and prepare the cell for division by establishing the bipolar spindle during mitosis. A balance of kinase and phosphatase activity regulates centrosome number and mitotic spindle function. PPP1R2 is a negative regulator of Protein Phosphatase 1, PP1, and an activator of Aurora A Kinase, AURKA. Both PP1 and AURKA play critical roles in centrosome regulation, however PPP1R2's role at the centrosome has not been examined. Given that PPP1R2 interacts with PP1 and AURKA, critical regulators of the centrosome, I hypothesized that PPP1R2 is a key regulator of the centrosome cycle through its interaction with AURKA and PP1. I tested this hypothesis through an overexpression model using PPP1R2, PPP1R2 truncation mutant, PPP1R2 phosphomutant, AURKA, and PP1 plasmid constructs. PPP1R2, AURKA, and PP1 overexpression resulted in both supernumerary centrosomes and [gamma]-tubulin mislocalization. In addition, PPP1R2 truncation mutant overexpression resulted in similar effects at the centrosome. Only PPP1R2 phosphomimetic mutant overexpression resulted in increased centrosome number. PPP1R2 and PPP1R2 mutant overexpression also resulted in disruption of midbody architecture as well as polyploidy. PPP1R2 truncation mutant overexpression significantly decreased PP1 midbody localization while PPP1R2 as well as PPP1R2 phosphomimetic, PPP1R2E, mutant overexpression increased PP1 midbody localization.PPP1R2's regulation of PP1 midbody recruitment further supported PPP1R2's role in midbody regulation. Overall, I found that PPP1R2 does coordinate PP1 and AURKA activities to regulate the centrosome protein recruitment as well as centrosome number through midbody architecture maintenance. In addition, PPP1R2 was shown to regulate microtubule nucleation from the centrosome and this regulation was dependent on PPP1R2's phosphorylation state. Overall, this dissertation demonstrates that PPP1R2 is a critical regulator of centrosome as well as midbody structure and function through AURKA and PP1 activity coordination.
Keywords: PPP1R2; PP1; AURKA; Aurora A Kinase; Protein Phosphatase 1; Mitotic Spindle; Cell Division; Centrosome Cycle; Cell Cycle; Centrosomes; Spindle Apparatus; Biochemical Phenomena; Durable Medical Equipment; Phosphoric Monoester Hydrolases; Midbody